COVID-19, society and crime in Europe - Siegel, Dina; Dobryninas, Aleksandras; Becucci, Stefano (Studies of organized crime, 2022)
Introduction -- Part 1. East and Central Europe -- The Covid-19 Pandemic Crisis and its Impact on Crime Rates in Bulgaria -- Covid-19 and Crime in Serbia -- Pandemic and Infodemic in Lithuania -- Crime, Law Enforcement and Rule of Law in Time of the Covid-19 Pandemic in Poland -- Covid-19, Crime and Social Control in Slovenia -- Influence of Covid-19 Pandemic on Social Control, Crime Patterns and Life in Prison in Hungary -- Part 2. South Europe -- Crime, Criminal Policy and Social Reactions in Greece in the Era of Covid-19 -- The Covid-19 Pandemic in Italy: the Effects on Society and Crime -- Social and Criminal Impact of Covid-19 in Spain -- How did the Pandemics Shaped Crime and Justice in Portugal? -- Part 3. West and North Europe -- The Covid-19 Pandemic in Germany. Prevention Measures, Protest and the Impact on Crime Rates -- Covid-19: Policies, Trust and Crime in the Netherlands -- Patterns of Crime during the Covid-19 Pandemic in Belgium -- Violent Crime in Finland during the First Year of the Covid-19 Pandemic -- Violent Crime and Covid-19 in England and Wales -- Impact of the Covid-19 Pandemic on Crime in Switzerland in 2020. A First Assessment -- Conclusion -- Index.